2022
DOI: 10.1007/s10340-022-01582-5
|View full text |Cite|
|
Sign up to set email alerts
|

Insect netting: effect of mesh size and shape on exclusion of some fruit pests and natural enemies under laboratory and orchard conditions

Abstract: To improve exclusion systems for fruit trees, insect nets of various types were evaluated for their permeability to different beneficial and pest species, under laboratory and field conditions. Pests studied were the apple maggot, Rhagoletis pomonella (Diptera: Tephritidae) and the spotted wing drosophila, Drosophila suzukii (Diptera: Drosophilidae). Beneficials were Aphidoletes aphidimyza (Diptera: Cecidomyiidae), Aphidius matricariae (Hymenoptera: Braconidae) and Aphelinus abdominalis (Hymenoptera: Aphelinid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…It has been observed in previous studies that there is potential for outbreaks of secondary pests such as the European red mite, aphids, and leafrollers under netting systems ( Marshall and Beers 2021 , 2022 , Chouinard et al 2022 ). While we did not observe any secondary pest infestations in this study, or any fruit damage or physiological symptoms of such pests under the netting, additional investigation into colonization under hail netting in Minnesota is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been observed in previous studies that there is potential for outbreaks of secondary pests such as the European red mite, aphids, and leafrollers under netting systems ( Marshall and Beers 2021 , 2022 , Chouinard et al 2022 ). While we did not observe any secondary pest infestations in this study, or any fruit damage or physiological symptoms of such pests under the netting, additional investigation into colonization under hail netting in Minnesota is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In North America, there have been several studies documenting the effectiveness of different types of exclusion netting for insect pests in apple ( Chouinard et al 2016 ). In Quebec, Canada, a 5-yr study documented the effectiveness of a single row, complete exclusion netting system (1.9 × 0.95 mm mesh) that prevented damage from the apple maggot, codling moth, and the tarnished plant bug ( Lygus lineolaris Palisot de Beauvois, Hemiptera: Miridae) ( Chouinard et al 2017 , 2022 ). More recently, a study in Washington found that codling moth could be excluded by using net cages (2 × 5 mm mesh) placed around large orchard blocks ( Marshall and Beers 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Recently Tait et al deeply reviewed the current knowledge on the D. suzukii control strategies highlighting future perspectives for a more sustainable and eco-friendly integrated pest management (IPM), 25 through the implementation of cultural, physical, genetic techniques and behavioral manipulation. [26][27][28] However, biological control has been considered as the most promising approach to manage D. suzukii and several methods have been set up, 29,30 including the intentional importation of the Asian Ganaspis brasiliensis Ihering (Hymenoptera: Figitidae), which is the best candidate for the classical biological control program among a panel of several co-evolved larval parasitoids. [31][32][33][34] However, the success of a classical biological control program requires the fulfillment of social, political and economic matters, as well as multiple field evaluations over the year.…”
Section: Introductionmentioning
confidence: 99%